Respuesta :
2x + 8y = –2 --------- (1)
5x + 6y = 9 --------- (2)
(1) x 5 : 10x + 40y = -10 ----------- (1a)
(2) x 2 : 10x + 12y = 18 ----------- (2a)
(1a) - (2a) : 28y = -28
y = -1
Substitute y = -1 into (1)
2x + 8(-1) = –2
2x - 8 = -2
2x = 6
x = 3
Answer : (3, -1) (Answer A)
5x + 6y = 9 --------- (2)
(1) x 5 : 10x + 40y = -10 ----------- (1a)
(2) x 2 : 10x + 12y = 18 ----------- (2a)
(1a) - (2a) : 28y = -28
y = -1
Substitute y = -1 into (1)
2x + 8(-1) = –2
2x - 8 = -2
2x = 6
x = 3
Answer : (3, -1) (Answer A)
To find the y:
2x + 8y = –2
5x + 6y = 9
(2x + 8y = –2) -5
(5x + 6y = 9) 2
-10x - 40y = 10
10x + 12y = 18
-28y = 28
y = -1
-----------------------------------------------------------------------------------------------------------------
To find the x:
5x + 6y = 9
5x + 6(-1) = 9
5x - 6 = 9
5x = 15
x = 3
-----------------------------------------------------------------------------------------------------------------
Check:
2x + 8y = –2
2(3) + 8(-1) = -2
6 - 8 = -2
-2 = -2
-----------------------------------------------------------------------------------------------------------------
Solution: (3,-1)
2x + 8y = –2
5x + 6y = 9
(2x + 8y = –2) -5
(5x + 6y = 9) 2
-10x - 40y = 10
10x + 12y = 18
-28y = 28
y = -1
-----------------------------------------------------------------------------------------------------------------
To find the x:
5x + 6y = 9
5x + 6(-1) = 9
5x - 6 = 9
5x = 15
x = 3
-----------------------------------------------------------------------------------------------------------------
Check:
2x + 8y = –2
2(3) + 8(-1) = -2
6 - 8 = -2
-2 = -2
-----------------------------------------------------------------------------------------------------------------
Solution: (3,-1)